TELAAH PEMIKIRAN ISMĀ'ĪL RAJI AL-FARŪQĪ TENTANG ISLAMISASI SAINS DAN IMPLEMENTASINYA PADA PENDIDIKAN NASIONAL - Deni Kurniadi, -; Misnawati, -; Dhirgham Djabar Kurniadi, - (2021)
The effect of Western hegemony and domination raises it's own concerns, especially for the condition of Muslim education. The progress of the West which is secular, makes education and science separate from theological values. Departing from these problems, the researcher attempted to examine Ismā'īl Raji al-Farūqī's thoughts on the Islamization of science as a solution to these problems. This study aims to describe the concept of Islamization of science initiated by Ismā'īl Raji al-Farūqī and to find out how the Islamization of science is implemented in national education. In this study, a qualitative approach was used, while the research instrument was the researcher himself. Collecting data in this study used library research techniques, while research data analysis was carried out by reducing data, presenting data, and drawing conclusions or verification. From this research, it is found that the concept of Islamization of science is an integration of religion and science, in which this integration is based on the essence of Islam itself, namely tauhid. The Islamization of science exists to protect science and education from the secular impact of the West which dichotomizes reason and revelation. This effort to Islamize science is carried out as a solution to the malaise that afflicts Muslims in various aspects of life. Ismā'īl Raji al-Farūqī's thought about the Islamization of science is implemented in national education although not completely and completely. This can be seen in the objectives of national education in Pasal 3 UU No.20 Tahun 2003, namely forming students into human beings who believe and fear God Almighty, as well as the existence of Kompetensi Inti-1 (KI-1) in every subject seeks to incorporate religious values into various fields of knowledge that students learn.